Maintenance of rare tree species in the mixed dipterocarp forests of Sarawak, East Malaysia, with implications for conservation biology - Primack, Richard B. (Boston Univ., MA (USA). Dept. of Biology) (2013)
The majority of tree species in tropical rain forests are rare on a local scale. A major problem in ecology is to investigate how these species can persist at such low density. Studying rare species is difficult since the population sizes of rare species are small. A related problem involves the demographic factors preventing any of the more common species from achieving dominance in the forest such as happens in the temperate zone. To investigate this topic, tree populations in three contrasting mixed dipterocarp forests in Sarawak have been followed for 20 years. At each forest, marked trees have been measured at five year intervals to gain information on rates of tree growth, recruitment and survival. The strengths and weaknesses of our methodology are constrasted with alternative experimental designs to highlight the best approaches for investigations of biodiversity. We have compared rare, occasional and common species by combining species into density categories. In addition, the stability of population size is determined by establishing 50 percent confidence intervals for recruitment and survival rates. Using such approaches, long-term demographic studies can suggest the degree of temporal stability of rainforest communities, and give practical suggestions for preserving tree species in nature reserves.